Financing information and communication infrastructure needs in the developing world : public and private roles. (World Bank working paper, 2005)
Over the past ten years, private-sector-led growth has revolutionized access to telecommunications. Every region of the developing world benefitted in terms of investment and rollout. This revolution would have been impossible without government reform and oversight. Advanced information and communication infrastructure (ICI) are increasingly important to doing business in a globalizing world. Governments, enterprises, civil society, workers, and poor populations in the developing countries need more affordable access. This report proposes strategies that governments can carry out to attract p.